(untitled) (Research, Society and Development, 2022)
Objective: To analyze the scientific evidence available in the literature on the use of birth plan educational technologies with pregnant women. Methodology: This is an integrative literature review. We chose to search in Scielo, Latin American and Caribbean Literature on Health Sciences, Nursing Database, ScieVerse Scopus, PubMed. Data collection occurred from April to August 2021. The PICOT strategy was used to select the guiding question: What is the available scientific evidence on the use of technologies for birth planning among pregnant women? Inclusion criteria were scientific productions on the review theme, complete original articles, published in Portuguese, Spanish and English, without a time frame. Publications with only an abstract, without the delimitation adopted in the questioning, reflections, reviews, editorials, literature reviews, dissertations, and theses were excluded. Repeated studies were counted only once. Results: Fifteen studies were identified with evidence N1, N2, N3, N4, N6. Conclusion: The use of technologies on the birth plan with pregnant women is still incipient the Education Technology are increasingly present in everyday life such as: educational video, apps, text messages, birth plan, virtual learning object, artistic exhibition, document of refusal of procedures, web-based decisions, conversation wheel and leaflet.